"Amicus curiae" en el plano internacional - Losardo, Martín Francisco (2014)
Before analyzing the procedural institution of the amicus curiae throughout\nan array of international judicial bodies, the phenomenon known as ?fragmentation\nof International Law? must be considered. This initial background will enable\nus to achieve a better understanding of the way this institution is used in the different\ninternational jurisdictions, and it will help us drawing certain distinctions within them.\nSubsequently, we will study the amicus curiae itself, its development and its application\nin general terms. Finally, we will pay particular attention to the way this institution\nis employed at an international level, the core of this research work